IELTS foundation. - Preshous, Andrew; Roberts, Rachael; Preshous, Joanna; Gakonga, Joanne (IELTS Foundation., 2012)
IELTS Foundation is a motivating and comprehensive course for studnets preparing to take the International English Language Testing System examination.